2019
DOI: 10.1002/htj.21591
|View full text |Cite
|
Sign up to set email alerts
|

A numerical approach for MHD Al2O3–TiO2/H2O hybrid nanofluids over a stretching cylinder under the impact of shape factor

Abstract: In this research, the heat transfer and magnetohydrodynamic stagnation point flow of a (Al 2 O 3 -TiO 2 /H 2 O) hybrid nanofluid past a stretching cylinder under the impact of heat generation, nonlinear thermal radiation, and nanoparticles shape factor has been analyzed using the Runge-Kutta-Fehlberg fifth order numerically method. The impact of changing diverse parameters, such as nanoparticles shape factor, named hexahedron and lamina, on temperature and velocity profiles and induced magnetic field, has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Specifications of different layers of power modules and nanofluid. 34,47,48 Material Thickness (cm) Density (kg/m 3 ) Thermal conductivity (W/m K) Specific heat capacity (J/kg K) increases. At the same time, the collision of the fluid with this separating blade vortex currents and leads to fluid turbulence behavior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifications of different layers of power modules and nanofluid. 34,47,48 Material Thickness (cm) Density (kg/m 3 ) Thermal conductivity (W/m K) Specific heat capacity (J/kg K) increases. At the same time, the collision of the fluid with this separating blade vortex currents and leads to fluid turbulence behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Applying nanoparticles in a fluid undoubtedly changes the physical properties of materials. In order to calculate the physical properties of the nanofluids used in the problem, the following equations can be used 47,48 :…”
Section: The Governing Equations (Nanofluid)mentioning
confidence: 99%
See 2 more Smart Citations
“…They used three different nanoparticles (Cu, Al 2 O 3 , and TiO 2 ) with water as base fluid. Some relevant studies on nanofluids can be observed …”
Section: Introductionmentioning
confidence: 99%